Design of an adaptive nonsingular terminal sliding model control method for a bearingless permanent magnet synchronous motor. (December 2017) - Xu, Bo; Shi, Guoding; Ji, Wei; Liu, Feiyu; Ding, Shihong; Zhu, Huangqiu
This paper presents an adaptive nonsingular terminal sliding mode controller for a bearingless permanent magnet synchronous motor. In order to rapidly converge state variables associated with terminal sliding mode control, an adaptive variable-rated exponential reaching law, in which the L 1 norm of state variables is introduced, is proposed for the second-order uncertain nonlinear dynamical system. Exponential and constant reaching speed can adaptively adjust according to the distance between state variable and equilibrium point, which can shorten the reaching time and weaken system chattering. The mathematical models for rotating speed and the rotor radial displacement of the bearingless permanent magnet synchronous motor system are set up. The proposed method is then applied to the speed and radial displacement control. Simulation results are provided to validate the effectiveness of the proposed method.